CONTRIBUTIONS OF SEED PHYSICAL AND CHEMICAL CHARACTERS OF VARIOUS SORGHUM GENOTYPES (SORGHUM BICOLOR [L.] MOENCH.) TO DAMAGED SEED INDUCED BY WEEVIL (SITOPHILUS SP.) DURING STORAGE - Pramono, Eko; Kamal, Muhammad; Susilo, Franciscus Xaverius; Timotiwu, Paul Benyamin (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2018)
Contributions of Seed Physical and Chemical Characters of Various Sorghum Genotypes (Sorghum bicolor [L.] Moench.) to Damaged Seed Induced by Weevil (Sitophilus sp.) During Storage. The percentage of damaged seeds due to feeding by Sitophilus sp. during storage varied among sorghum genotypes (Sorghum bicolor [L.] Moench.). Some researchers reported that the difference was influenced by the physical and chemical characters of the seed grains. This study aimed to determine the contribution of seed physical and chemical characters and their effect model on the percentage of damaged seeds due to weevil attack during storage. Measurement of damaged seeds was carried out on 34 sorghum genotypes after they were stored for four months under storage temperatures of 26 ºC and 18 ºC. Physical characters included seed hardness, weights of a thousand grains, pericarp thickness, and seed volume. Chemical characters of seeds included lipid, protein, carbohydrate, and tannin contents. Results of the study indicate that contribution of physical and chemical characters of sorghum seeds and their effect model on the percentage of damaged seeds due to weevil attack was different among storage under temperature of 26 ºC and under temperatures of  18 ºC.